EMG activity does not change during a time trial in competitive cyclists - Duc, S.; Betik, A. -C.; Grappe, F. (International Journal of Sports Medicine, 2005)
The purpose of the present study was to measure the electromyographic (EMG) activity of four lower limb muscles and the propulsive torque during a cycling time-trial (TT). Nine competitive cyclists (V·O2max: 73.8 ± 5.3 ml · min-1 · kg-1) performed two tests separated over a one-week period on a friction-load cycle ergometer equipped with a SRM crankset scientific system: 1) a continuous incremental test for the determination of the peak power output (PPO); and 2) a 30-min TT test at a self-selected work intensity. The EMG activity of the vastus medialis (VM), the rectus femoris (RF), the biceps femoris (BF), and the gastrocnemius medialis (GAS), and the propulsive torque were recorded every 5 min for 10 s. There was no time effect on the power output, the pedalling cadence, and the mean propulsive torque. The EMG activity of the VM and the RF muscles was unchanged during the TT (p > 0.05). The EMG activity of the two knee flexor muscles (BF and GAS) tended to increase with time but it was not significant (p > 0.05). The EMG/torque of the VM and the RF muscles tended to decrease with time but it was not significant (p > 0.05). The lack of increase in the EMG activity of the four investigated muscles seems to indicate that the subjects performed the TT test at a muscular work steady-state.